1996
DOI: 10.1126/science.271.5249.656
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Cells of the Primate Retina: Cone Specificity Without Spectral Opponency

Abstract: The chromatic dimensions of human color vision have a neural basis in the retina. Ganglion cells, the output neurons of the retina, exhibit spectral opponency; they are excited by some wavelengths and inhibited by others. The hypothesis that the opponent circuitry emerges from selective connections between horizontal cell interneurons and cone photoreceptors sensitive to long, middle, and short wavelengths (L-, M-, and S-cones) was tested by physiologically and anatomically characterizing cone connections of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
233
0
5

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(258 citation statements)
references
References 23 publications
20
233
0
5
Order By: Relevance
“…Verweij et al (2003) showed that the receptive fields of individual cone photoreceptors have surrounds that get mixed L and M cone input. H1 horizontal cells, thought to contribute to the inhibitory surrounds of midget bipolar and ganglion cells, get nonselective input from L and M cones (Wässle et al, 1989;Dacheux and Raviola, 1990;Goodchild et al, 1996;Dacey et al, 1996Dacey et al, , 2000b. There is no evidence that midget bipolar cells, which are the middle elements in the private line connections from cones to midget ganglion cells, have selective surround circuitry.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Verweij et al (2003) showed that the receptive fields of individual cone photoreceptors have surrounds that get mixed L and M cone input. H1 horizontal cells, thought to contribute to the inhibitory surrounds of midget bipolar and ganglion cells, get nonselective input from L and M cones (Wässle et al, 1989;Dacheux and Raviola, 1990;Goodchild et al, 1996;Dacey et al, 1996Dacey et al, , 2000b. There is no evidence that midget bipolar cells, which are the middle elements in the private line connections from cones to midget ganglion cells, have selective surround circuitry.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, although the relative weight of L and M cone input to the midget receptive field varied from cell to cell, this variability was closely matched by that of parasol cells with overlapping receptive fields. Finally, we compared the relative strengths of L and M cone inputs to ganglion cells to the inputs to H1 horizontal cells, whose dendrites sum input from L and M cones (Dacey et al, 1996). The relative strengths of L and M cone input to H1 cells also varied from cell to cell (Dacey et al, 2000b) but were highly correlated with the inputs to ganglion cells at the same retinal locations.…”
Section: Introductionmentioning
confidence: 99%
“…We used a full-field square-wave stimulus to facilitate searching for the cell; when we penetrated a horizontal cell, we saw a change in the resting potential (Ϫ38.8 Ϯ 6.5; n ϭ 8) and the typical shape of the step response (see Fig. 7C) (Lankheet et al, 1992;Dacey et al, 1996). Not all horizontal cells were stained, and not all recorded cells could be identified as A type or B type.…”
Section: Methodsmentioning
confidence: 99%
“…This discrepancy led us to suggest that H2 horizontal cells, which collect M/L input and feedback negatively to S-cone terminals (Ahnelt and Kolb, 1994a,b;Dacey et al, 1996;Lee et al, 1999;Verweij et al, 2003), provide each S-cone with a yellow-OFF receptive field coextensive with its intrinsic blue-ON field .…”
Section: The Critical Locus For By Color Visionmentioning
confidence: 99%